2014
DOI: 10.3109/02713683.2014.973043
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Macular Choroidal Thickness with Concentrations of Aqueous Vascular Endothelial Growth Factor in High Myopia

Abstract: Macular choroidal thickness was significantly correlated with aqueous, but not serum, levels of VEGF in highly myopic eyes. Macular choroidal thickness may be of predictive value for identifying aqueous VEGF levels in high myopia patients and may, thus, be a useful prognostic modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…These findings are in agreement with those reported by Shin et al ,13 14 who found significantly lower VEGF levels in the aqueous humour of highly myopic patients compared with non-myopic subjects, whereas PEDF concentrations did not differ significantly between groups. Chen et al 15 recently demonstrated that aqueous VEGF levels in highly myopic patients were significantly lower than controls. Moreover, as ascertained by Chan et al ,16 in patients with mCNV, intravitreal anti-VEGF injections increase PEDF levels about 6–7 times from baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in agreement with those reported by Shin et al ,13 14 who found significantly lower VEGF levels in the aqueous humour of highly myopic patients compared with non-myopic subjects, whereas PEDF concentrations did not differ significantly between groups. Chen et al 15 recently demonstrated that aqueous VEGF levels in highly myopic patients were significantly lower than controls. Moreover, as ascertained by Chan et al ,16 in patients with mCNV, intravitreal anti-VEGF injections increase PEDF levels about 6–7 times from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The most plausible explanation for the lower VEGF concentration found in the aqueous humour of patients with mCNV is due to the dilution effect in the anterior chamber and vitreous cavity of myopic patients since the axial length is longer and therefore the intraocular volume is larger in patients with high myopia 9. However, in patients with PM, a significant correlation between axial length and macular choroidal thickness and VEGF levels has also been demonstrated 15. Moreover, diminished VEGF production in high myopia could be due to generalised retinal pigment epithelium (RPE) cell degenerative changes, which lead to photoreceptor degeneration 18.…”
Section: Discussionmentioning
confidence: 99%
“…The trend of which was similar to the decreased vascular endothelial growth factor (VEGF) which was found to have a negative correlation with the axial length. 3537 VEGF produced by vascular endothelial cells and retinal pigment epithelium (RPE) cells, may play a key role in the development of retinal vasculature by stimulating the vessel growth. 35,38,39 The decreased aqueous VEGF level found in high myopia may also contribute to the possible loss of capillary network.…”
Section: Discussionmentioning
confidence: 99%
“…3537 VEGF produced by vascular endothelial cells and retinal pigment epithelium (RPE) cells, may play a key role in the development of retinal vasculature by stimulating the vessel growth. 35,38,39 The decreased aqueous VEGF level found in high myopia may also contribute to the possible loss of capillary network. 29,31 It is possible that, with the progress of myopia, the thinned retina due to the elongated axial length can cause the degeneration of retinal vascular endothelial cells and retinal pigment epithelium (RPE) cells, resulting in consequential decreases in VEGF production and microvessel density.…”
Section: Discussionmentioning
confidence: 99%
“…2024 Much of the difficulty in achieving reliable choroidal thickness measurements is due to the variable and often obscure appearance of the choroidal-scleral junction (CSJ) that determines the posterior boundary of the choroid. While some studies appear to use the border of the choroidal vascular lumen as the posterior boundary, 15,2528 others defined the border of the choroid stroma or sclera as the CSJ. 2932 In some individuals, there is also a hyporeflective band corresponding to the suprachoroidal layer, which may further contribute to variability in choroidal thickness measurements.…”
Section: Introductionmentioning
confidence: 99%